BIBLIOMETRIC ANALYSIS OF MSMEs FINANCING IN ISLAMIC BANKING - Sahal, Sakinah; Asyik, Syaifullah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
This study aims to identify the development map of research on MSMEs financing in Islamic banking with a literature review approach. The object of this research is the mapping of research literature related to MSMEs financing in Islamic banking, as well as providing relevant policy recommendations for Islamic banking and researchers in the future. The research data sources come from international journals indexed in Google Scholar, Sinta, and Scopus. The data analysis techniques used include: mapping RIS (Research Information Systems) data files on Mendeley Desktop based on the order of year, author, and publisher; mapping the results of bibliometric network visualisation and scientific publication trends using VOSviewer software; and mapping research topics. Based on bibliometric mapping, research on MSMEs financing is grouped into 12 clusters with 88 items. This research can be a reference for further research. The main objective of this research is to map the topic of MSMEs financing in Islamic banking using bibliometric methods to analyse and visualise the development of literature in this field through metadata network maps from indexed international journals and accredited journals.